The Drosophila ramshackle gene encodes a chromatin-associated protein required for cell morphology in the developing eye. - D'Costa, A.; Reifegerste, R.; Sierra, S.; Moses, K. (Mechanisms of Development, 2006)
We have identified ramshackle (ram) as a dominant suppressor of hedgehog loss-of-function in the developing Drosophila eye. We have characterized the gene and it encodes a double bromodomain protein with eight WD40 repeats. The Ram protein is localized predominantly to polytene chromosome interbands and is required for the transcription of some genes. ram is an essential gene and null mutants die during larval life. In the developing retina, ram mutant cells have morphological defects including disrupted apical junctions, disorganized actin cytoskeletons and mislocalized nuclei, which are followed by delays in cell-cycle transitions and the expression of differentiation markers. ram is a conserved gene: its vertebrate homolog (WDR9), which lies in Down's Syndrome Critical region 2 (DCR2) is also known to be associated with Brahma-Related-Gene 1 (BRG1).